The most suitable English learning methods for young learners - Masrurotul Ajiza (LEOTECH: Journal of Learning Education and Technology, 2024)
The aim of this article was to know the most suitable and effective methods to apply to young learners as elementary graders. The researcher got 17 female and male students. Their grade varied from class 1 to class 6. Before conducting this study, the problems faced by the students are they seemed got difficulty memorizing English words, lacked motivation, and lacked concentration in learning English. There were 3 methods used in this study: Grammar Translation Method (GTM), Audio Lingual Method, dan Total Physical Response. The students were taught English once a week. The researcher observed the effectiveness of each method in each meeting. Those methods were used all together in each learning process. The finding showed that GTM was not effective to apply, while the two latter were good and effective to apply for those students.